Nomogram including indirect bilirubin for the prediction of post-stroke depression at 3 months after mild acute ischemic stroke onset - Wang, Yanyan; Sun, Wenzhe; Miao, Jinfeng; Zhu, Zhou; Liang, Wenwen; Qiu, Xiuli; Pan, Chensheng; Li, Guo; Lan, Yan; Zhao, Xin; Xu, Yi (Frontiers in Neurology, 2023)
Background: Post-stroke depression (PSD) has been proved to be associated with stroke severity. Thus, we hypothesized that the prevalence of PSD would be lower in patients with mild stroke. And we aim to explore predictors of depression at 3 months after mild acute ischemic stroke (MAIS) onset as well as develop a practical and convenient prediction model for early identification of high-risk patients. Methods: A total of 519 MAIS patients were consecutively recruited from three hospitals of Wuhan city, Hubei province. MAIS was defined as the National Institute of Health Stroke Scale (NIHSS) score≤5 at admission. Meeting the DSM-V diagnostic criteria and17-item Hamilton Rating Scale for Depression (HAMD-17) > 7 at 3-month follow-up were considered the primary outcome. A multivariable logistic regression model was used to determine the factors adjusted for potential confounders and all independent predictors were brought into the construction of a nomogram to predict PSD. Results: The prevalence of PSD up to 32% at 3 months after MAIS onset. After adjusting by potential confounders, Indirect bilirubin (p=0.029), Physical activity (p=0.001), Smoking (p=0.025), Hospitalization days (p=0.014), Neuroticism (p<0.001) and MMSE(p＜0.001) remained independently and significantly related with PSD. The concordance index (C-index) of the nomogram jointly constructed by the above 6 factors was 0.723(95%CI:0.678-0.768). Conclusions: The prevalence of PSD seems equally high even if the ischemic stroke is mild, which calls for great concern from clinicians. Besides, our study found that higher level of indirect bilirubin can lower the risk of PSD. This finding may provide a potential new approach for PSD treatment. Furthermore, the nomogram including bilirubin is convenient and practical to predict PSD after MAIS onset.